2011
DOI: 10.1007/s11596-011-0387-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal plasma suppresses bacterial colonization on skin wound and promotes wound healing in mice

Abstract: The present study evaluated the effect of non-thermal plasma on skin wound healing in BalB/c mice. Two 6-mm wounds along the both sides of the spine were created on the back of each mouse (n=80) by using a punch biopsy. The mice were assigned randomly into two groups, with 40 animals in each group: a non-thermal plasma group in which the mice were treated with the non-thermal plasma; a control group in which the mice were left to heal naturally. Wound healing was evaluated on postoperative days (POD) 4, 7, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 22 publications
(21 reference statements)
3
35
0
2
Order By: Relevance
“…The wound area was significantly more reduced in the rats treated with NTP than in that of the untreated rats on day 7, and also histological analysis confirmed an enhanced epithelisation and a reduced granulation tissue area after plasma treatment. Respectively, improved wound contraction after the plasma treatment has also been confirmed in other studies using NTP generated from argon, helium or nitrogen1678910111213141516171830.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The wound area was significantly more reduced in the rats treated with NTP than in that of the untreated rats on day 7, and also histological analysis confirmed an enhanced epithelisation and a reduced granulation tissue area after plasma treatment. Respectively, improved wound contraction after the plasma treatment has also been confirmed in other studies using NTP generated from argon, helium or nitrogen1678910111213141516171830.…”
Section: Discussionsupporting
confidence: 68%
“…While most of the already published studies on wound healing were carried out using argon plasma161718, we applied air plasma, which generates high amounts of reactive nitrogen species, such as nitric oxide (NO), nitrogen dioxide (NO 2 ) and reactive oxygen species such as ozone (O 3 ), superoxide (O 2 − ) and hydroxyl radicals (∙OH). In contrast to air plasma, the composition of the argon plasma significantly differs, and only low amounts of reactive oxygen and nitrogen species are produced, by mixing the argon plasma with the ambient air.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One promising strategy to achieve this goal is the application of cold atmospheric pressure plasma . Yu et al found that cold plasma facilitated wound healing by suppressing bacterial colonization . In vitro human and in vivo animal data from Arndt et al suggested that 2 min of treatment with their MicroPlaSter cold plasma generating device was an effective technique for activating the production of wound healing‐related molecules in dermal fibroblasts and resulted in improved wound healing .…”
mentioning
confidence: 99%